Mechanics of electrophoresis-induced reversible hydrogel adhesion. (April 2019) - Xin, An; Zhang, Runrun; Yu, Kunhao; Wang, Qiming
Abstract: Adhesion of soft materials is a double-edged sword that can induce both advantages and disadvantages. On-demand control of the adhesion of soft materials with external stimuli is naturally desirable. Electrophoresis-induced hydrogel adhesion is such a technology that induces electrically-triggered reversible adhesion and may be useful for various engineering applications. Despite the potential, the detailed mechanism is still elusive. Here, we establish an analytical theory framework to model the electrophoresis-induced reversible adhesion. We consider that during the electrophoresis process, free charged chains are driven by the electric field to move across the interface to interpenetrate into the respective material matrix, and form weak ionic bonds with chains with opposite charges. We model the interpenetration of the charged polymer chains as an electrically-driven diffusion-reaction process. The chain diffusion follows an electrically-driven reptation-like motion, and cationic-anionic bond formation follows a bell-like chemical reaction. We predict that the electrophoresis-induced adhesion increases with the electrophoresis time and reaches a plateau as the electrophoresis process is long enough. We theoretically study the effects of the electric force, the polymer chain length, and the chain friction coefficient on the hydrogel adhesion. We also predict that under reverse electrophoresis the hydrogel adhesion decreases with the process time. Our theoretical results agree well with the experiments for both electrophoresis-induced adhesion and adhesion releasing. We expect our theoretical model may facilitate the quantitative understanding and optimization of various methods for actively controlling the adhesion of soft materials.